A kind of left-handed polylactic acid microsphere for drug delivery system and its preparation method and application with controllable degradation rate

CN121930499BActive Publication Date: 2026-10-16SHANGHAI SHUANGSHEN MEDICAL INSTRUMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610173735.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-02-06
Publication Date
2026-10-16
Estimated Expiration
2046-02-06

AI Technical Summary

Technical Problem

微球的球形结构及生物降解性可以实现药物的缓慢释放,从而显著延长药物作用时间,减少给药频率,但传统的左旋聚乳酸微球的降解存在药物释放不均,局部炎症和性能难以预测等问题

Benefits of technology

(1)本发明采用乳酸-羟基乙酸-聚乙烯醇嵌段共聚物和左旋聚乳酸进行混合,作为左旋聚乳酸微球的原料主体成分,可以调控微球粒径、表面形貌和孔径的分布,得到降解速率可控的左旋聚乳酸微球。制备得到的左旋聚乳酸微球产品具有良好表面形貌结构、生物相容性、生物可降解性和高度药物负载效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121930499B_ABST
    Figure CN121930499B_ABST
Patent Text Reader

Abstract

The application relates to a kind of left-handed polylactic acid microspheres for drug delivery system and with controllable degradation rate and its preparation method and application, the preparation method includes that oil phase organic solution is added into emulsifier aqueous solution by SPG membrane, stirring is carried out, left-handed polylactic acid microspheres crude product is obtained, left-handed polylactic acid microspheres crude product is sequentially mixed with sodium hydroxide solution, polylysine solution and is reacted, is washed, freeze-drying is obtained left-handed polylactic acid microspheres;The solute in the oil phase organic solution includes left-handed polylactic acid and lactic acid-hydroxyacetic acid-polyvinyl alcohol block copolymer.The left-handed polylactic acid microspheres material obtained by the specific preparation process has good stability and biocompatibility, and the degradation rate is controllable, and is suitable for preparing drug delivery system, to improve the curative effect of drug and reduce the frequency of administration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of drug delivery technology, and relates to a L-polylactic acid microsphere for use in drug delivery systems with controllable degradation rate, its preparation method and application. Background Technology

[0002] Traditional dosage forms or carriers in drug delivery systems have many limitations, making the development of novel drug carriers a major research direction in current drug delivery systems. Polylactic acid microspheres, with their inherent biodegradability, biocompatibility, and stability, can specifically address these key issues. Current drug delivery systems suffer from problems such as uncontrollable drug release, poor targeting, burst release effects, insufficient delivery efficiency, and non-degradable materials, making it difficult to meet the requirements of current multifunctional synergistic therapies.

[0003] L-lactic acid (L-LLA) microspheres have a compact structure with few or no pores on their surface. They are used to encapsulate drugs, and compared to other drug carriers and medical fillers, L-LLA microspheres exhibit superior biocompatibility and biodegradability. L-LLA microspheres can ultimately degrade into carbon dioxide and water in the human body, avoiding immune responses and toxicity accumulation caused by long-term retention. They are ideal carriers for sensitive drugs such as peptides and proteins, and are also suitable for long-term retention in cosmetic filling applications. The spherical structure and biodegradability of the microspheres enable slow drug release, significantly prolonging the duration of drug action and reducing the frequency of administration. However, the degradation of traditional L-LLA microspheres presents problems such as uneven drug release, local inflammation, and unpredictable performance. Therefore, developing L-LLA microsphere carriers that meet the requirements of controllable microsphere degradation, high drug loading, sustained release, and safety in current drug delivery systems has become an urgent need.

[0004] Traditional L-type polylactic acid (PLA) microspheres are highly dependent on their initial molecular weight and crystallinity for degradation rate due to the inherent properties of the material. The degradation of L-type PLA microspheres is primarily caused by the random hydrolysis of polylactic acid ester bonds. This leads to simultaneous internal and external degradation of the microspheres during the degradation process, causing them to lose structural integrity and disintegrate in the mid-degradation stage. Therefore, the key challenge in developing novel L-type PLA microspheres is how to specifically control the hydrolysis of ester bonds during PLA degradation while maintaining the structural integrity of the microspheres throughout the degradation process. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a L-polylactic acid microsphere with controllable degradation rate for use in drug delivery systems, as well as its preparation method and applications. To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing L-polylactic acid microspheres for use in drug delivery systems with controllable degradation rates, the preparation method comprising the following steps: The oil phase organic solution was added to the emulsifier aqueous solution through an SPG membrane and stirred to obtain crude L-polylactic acid microspheres. The crude L-polylactic acid microspheres were then mixed and reacted with sodium hydroxide solution and polylysine solution in sequence. After washing and freeze-drying, L-polylactic acid microspheres were obtained. The solutes in the oil phase organic solution include L-polylactic acid and lactic acid-glycolic acid-polyvinyl alcohol block copolymer.

[0006] This invention utilizes a combination of lactic acid-glycolic acid-polyvinyl alcohol block copolymer and L-polylactic acid (PLA) to prepare L-PLA microspheres. Compared to PLA, the lactic acid-glycolic acid-polyvinyl alcohol block copolymer has a four-armed star structure, a higher molecular weight, and a polyhedral microstructure. The combined use of these two materials with SPG film emulsification yields L-PLA microspheres with highly uniform particle size and controllable degradation rates. This effectively overcomes the problem of traditional pure L-PLA microsphere preparation being heavily influenced by the material itself, with degradation rates heavily dependent on initial molecular weight and crystallinity.

[0007] Furthermore, by using an SPG membrane for the reaction, the dispersed phase can be slowly passed through the uniform pores of the SPG membrane under pressure, forming tiny droplets at the pore openings. The continuous phase flows on the membrane surface, and the droplets remain stable after being washed away, forming a microsphere emulsion with uniform particle size.

[0008] Preferably, the preparation method of the lactic acid-glycolic acid-polyvinyl alcohol block copolymer includes the following steps: S1. Polyethylene glycol and benzyltriethylammonium chloride are mixed with sodium hydroxide solution, heated and stirred, epichlorohydrin is added dropwise, and stirring is continued. After the reaction is completed, the filtrate is collected by filtration, washed with dichloromethane, dried, evaporated and concentrated for recrystallization to obtain linear amphoteric epoxy polyethylene glycol. S2. Ply lactide, glycolide, stannous octoate and dichloromethane are mixed with pentaerythritol and reacted under a nitrogen atmosphere. After the reaction is completed, the mixture is centrifuged, the supernatant is removed, the precipitate is washed with anhydrous methanol and dried to obtain a solid product. S3. The linear amphoteric epoxy polyethylene glycol obtained in step S1 and the solid product obtained in step S2 are mixed and reacted with dilute sulfuric acid. Ammonium bicarbonate is added to quench the reaction, the supernatant is collected by centrifugation, and the supernatant is distilled under reduced pressure to obtain the lactic acid-glycolic acid-polyvinyl alcohol block copolymer.

[0009] In the above steps S1 and S2, there is no distinction between the order of the reactions.

[0010] The lactic acid-glycolic acid-polyvinyl alcohol block copolymer prepared by modifying polylactic acid in this invention is used in combination with L-polylactic acid as a raw material for preparing L-polylactic acid microspheres. Compared with the traditional preparation of pure L-polylactic acid, it can effectively control the hydrolysis of ester bonds during the degradation of polylactic acid, reduce the premature disintegration of microsphere structure caused by random hydrolysis, and effectively protect the integrity of microsphere structure during degradation.

[0011] Preferably, the temperature for heating and stirring in step S1 is 48-52℃ (e.g., 48℃, 49℃, 50℃, 51℃, 52℃, etc.); the heating and stirring time is 0.5-3 h (e.g., 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, etc.); the evaporation and concentration temperature is 110-130℃ (e.g., 110℃, 115℃, 120℃, 125℃, 130℃, etc.), and the time is 1-3 h, e.g., 1 h, 1.5 h, 2 h, 2.5 h, 3 h, etc.

[0012] Preferably, the reaction temperature in step S2 is 150-170℃ (e.g., 150℃, 155℃, 160℃, 165℃, 170℃, etc.); and the time is 6-10 h (e.g., 6 h, 7 h, 8 h, 9 h, 10 h, etc.).

[0013] Preferably, the temperature of the mixing reaction in step S3 is 60-70℃ (e.g., 60℃, 62℃, 65℃, 68℃, 70℃, etc.), and the time is 70-80 min (e.g., 70 min, 72 min, 75 min, 78 min, 80 min, etc.).

[0014] Preferably, the vacuum distillation in step S3 is carried out at a temperature of 110-130℃ (e.g., 110℃, 115℃, 120℃, 125℃, 130℃, etc.) and for a time of 1-3 h, e.g., 1 h, 1.5 h, 2 h, 2.5 h, 3 h, etc.

[0015] Preferably, the centrifugation speed in step S3 is 8000-12000 rpm (e.g., 8000 rpm, 9000 rpm, 10000 rpm, 11000 rpm, 12000 rpm, etc.); the time is 5-10 min (e.g., 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, etc.); and the temperature is 10-30℃ (e.g., 10℃, 15℃, 20℃, 25℃, 30℃, etc.).

[0016] Preferably, the raw materials for preparing the L-type polylactic acid microspheres, by mass fraction, include 10-15 parts of an oil phase organic solution, 150-200 parts of an emulsifier aqueous solution, 70-100 parts of a sodium hydroxide aqueous solution, and 70-100 parts of a polylysine aqueous solution.

[0017] The "10-15 portions" mentioned above can be, for example, 10, 11, 12, 13, 14, or 15 portions; The aforementioned "150~200 portions" could be, for example, 150, 160, 170, 180, 190, 200 portions, etc. The "70~100 portions" mentioned above can be, for example, 70, 75, 80, 85, 90, 95, 100 portions, etc.

[0018] In this invention, when the amounts of each raw material used to prepare the L-polylactic acid microspheres are within a specific range, the resulting L-polylactic acid microspheres have a higher uniformity of particle size and a better encapsulation effect on the drug.

[0019] Preferably, the solvent in the oil phase organic solution includes any one or a combination of at least two of dichloromethane, ethyl acetate, chloroform, acetone, tetrahydrofuran, or propylene carbonate.

[0020] Preferably, the concentration of the solute in the oil phase organic solution is 0.05-0.15 g / mL, for example, 0.05 g / mL, 0.06 g / mL, 0.08 g / mL, 0.1 g / mL, 0.12 g / mL, 0.15 g / mL, etc.

[0021] In this invention, when the concentration of the oil phase in the oil-phase organic solution is within a specific range, the production efficiency of the preparation reaction and the stability of the primary emulsion of the oil-phase organic solution can be effectively improved.

[0022] Preferably, the emulsifier in the aqueous emulsifier solution is any one or a combination of at least two of polyvinyl alcohol, Tween-80, gelatin, or polyvinylpyrrolidone; preferably polyvinyl alcohol.

[0023] The addition of emulsifiers allows them to adsorb onto small droplets of the oil-phase organic solution, resulting in lower surface tension and the formation of a robust interfacial film. The long-chain molecules of the emulsifier provide steric hindrance, preventing droplet collision and coalescence, thus ensuring the uniformity and smooth surface morphology of the polylactic acid (PLA) microspheres. The selection of the emulsifier is crucial for L-PLA microspheres, as it directly affects the particle size, pore size, porosity, surface morphology, and drug delivery performance of the microspheres.

[0024] Preferably, the concentration of the emulsifier in the aqueous emulsifier solution is 0.03-0.10 g / mL, for example, it can be 0.03 g / mL, 0.04 g / mL, 0.05 g / mL, 0.06 g / mL, 0.08 g / mL, 0.10 g / mL, etc.

[0025] When the concentration of the emulsifier in the aqueous emulsifier solution is within the specific range mentioned above, the prepared L-polylactic acid microsphere product will have better performance.

[0026] Preferably, the oil phase organic solution is added to the emulsifier aqueous solution via injection through an SPG membrane.

[0027] Preferably, the injection rate is 1-3 mL / min (e.g., 1 mL / min, 1.5 mL / min, 2 mL / min, 2.5 mL / min, 3 mL / min, etc.).

[0028] Preferably, the stirring speed for the reaction is 600-1200 rpm (e.g., 600 rpm, 900 rpm, 1000 rpm, 1100 rpm, 1200 rpm, etc.), the temperature is 10-16 h (e.g., 10 h, 11 h, 12 h, 14 h, 16 h, etc.), and the stirring temperature is 20-30℃ (e.g., 20℃, 21℃, 22℃, 25℃, 28℃, 30℃, etc.).

[0029] Preferably, the washing method is centrifugal washing.

[0030] Preferably, the centrifugal washing speed is 8000-12000 rpm (e.g., 8000 rpm, 9000 rpm, 10000 rpm, 11000 rpm, 12000 rpm, etc.); the time is 5-10 min (e.g., 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, etc.); and the temperature is 10-30℃ (e.g., 10℃, 15℃, 20℃, 25℃, 30℃, etc.).

[0031] Preferably, the method for preparing the L-polylactic acid microspheres for drug delivery systems with controllable degradation rate specifically includes the following steps: S1. Polyethylene glycol and benzyltriethylammonium chloride are mixed with sodium hydroxide solution, heated and stirred, epichlorohydrin is added dropwise, and stirring is continued. After the reaction is completed, the filtrate is collected by filtration, washed with dichloromethane, dried, evaporated and concentrated for recrystallization to obtain linear amphoteric epoxy polyethylene glycol. S2. Ply lactide, glycolide, stannous octoate and dichloromethane are mixed with pentaerythritol and reacted under a nitrogen atmosphere. After the reaction is completed, the mixture is centrifuged, the supernatant is removed, the precipitate is washed with anhydrous methanol and dried to obtain a solid product. S3. The linear amphoteric epoxy polyethylene glycol obtained in step S1 and the solid product obtained in step S2 are mixed and reacted with dilute sulfuric acid. Ammonium bicarbonate is added to quench the reaction, the supernatant is collected by centrifugation, and the supernatant is distilled under reduced pressure to obtain lactic acid-glycolic acid-polyvinyl alcohol block copolymer. S4. Mix L-polylactic acid, lactic acid-glycolic acid-polyvinyl alcohol block copolymer and drug to obtain an oil phase organic solution; S5. Following the steps, load the oil-phase organic solution primary emulsion obtained in step S4 into a syringe, inject it into the emulsifier aqueous solution through an SPG membrane and a syringe pump, stir to carry out the reaction, remove the organic solvent after the reaction is completed, centrifuge and wash to remove the emulsifier and oil-phase solvent, place it in sodium hydroxide solution for hydrolysis, centrifuge and wash, mix and react with polylysine solution, wash, freeze dry to obtain the final product. In the above steps S1 and S2, there is no distinction between the order of the reactions.

[0032] Preferably, the temperature for heating and stirring in step S1 is 48-52℃; the time for heating and stirring is 0.5-3 h; and the temperature for evaporation and concentration is 110-130℃, and the time is 1-3 h. The reaction in step S2 is carried out at a temperature of 150-170℃ for 6-10 hours. The mixing reaction in step S3 is carried out at a temperature of 60-70℃ for 70-80 min; the vacuum distillation is carried out at a temperature of 110-130℃ for 1-3 h; the centrifugation is carried out at a speed of 8000-12000 rpm for 5-10 min at a temperature of 10-30℃. The injection rate in step S5 is 1-3 mL / min; the stirring speed for the reaction is 600-1200 rpm, the temperature is 10-16 h, and the stirring temperature is 20-30℃; the centrifugation washing speed is 8000-12000 rpm, the time is 5-10 min, and the temperature is 10-30℃.

[0033] In a second aspect, the present invention provides a L-type polylactic acid microsphere material prepared according to the preparation method described in the first aspect.

[0034] Thirdly, the present invention provides the application of the L-polylactic acid microsphere material according to the second aspect in the preparation of products with drug delivery function.

[0035] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention uses a mixture of lactic acid-glycolic acid-polyvinyl alcohol block copolymer and L-polylactic acid as the main raw material component for L-polylactic acid microspheres. This allows for the control of the distribution of microsphere particle size, surface morphology, and pore size, resulting in L-polylactic acid microspheres with controllable degradation rate. The prepared L-polylactic acid microsphere products exhibit good surface morphology, biocompatibility, biodegradability, and high drug loading capacity.

[0036] (2) The present invention uses the SPG membrane method to prepare L-polylactic acid microspheres. The L-polylactic acid microspheres obtained have a uniform particle size distribution, good monodispersity, and controllable particle size.

[0037] (3) The preparation method of the present invention is simple to operate and the production process is simple and controllable. Attached Figure Description

[0038] Figure 1 This is a diagram of the L-type polylactic acid microsphere material prepared in Example 1; Figure 2 This is a scanning electron microscope image (bar: 10 μm) of the L-type polylactic acid microspheres prepared in Example 1. Figure 3 These are scanning electron microscope (SEM) images of the L-type polylactic acid microspheres prepared in Examples 2, 3, 4, and 6 (bar value in Example 2: 100 μm; bar value in Examples 3, 4-6: 10 μm). Figure 4 This is a schematic diagram of the experimental preparation of L-polylactic acid microspheres using an SPG membrane in Example 1; Figure 5 The molecular formula of the lactic acid-glycolic acid-polyvinyl alcohol block copolymer in the oil phase solute provided by this invention is: Figure 6 The graph shows the time relationship of natural degradation of four types of polylactic acid microspheres prepared under a near-human environment with different ratios of polylactic acid and lactic acid-glycolic acid-polyvinyl alcohol block copolymers; where A is Comparative Example 1, B is Example 1, C is Example 6, and D is Example 7. Detailed Implementation

[0039] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0040] The L-polylactic acid mentioned below is a product with a relative molecular mass of 110,000 from Shanghai Maclean Biochemical Technology Co., Ltd.

[0041] Preparation Example This preparation example provides a lactic acid-glycolic acid-polyvinyl alcohol block copolymer, which is prepared by the following method: (1) Add 3 g of polyethylene glycol and 1.5 g of benzyltriethylammonium chloride to 50 mL of sodium hydroxide solution with a concentration of 50 wt%, stir at 50 °C for 0.5 h, slowly add epichlorohydrin dropwise to the mixed solution, continue stirring for 2 h, filter the reaction solution after the reaction is completed, collect the filtrate, wash with dichloromethane and dry with anhydrous sodium sulfate, evaporate and concentrate for recrystallization to obtain linear amphoteric epoxy polyethylene glycol; (2) Using 0.3 g pentaerythritol as an initiator, under nitrogen protection, 10 g lactide, 3 g glycolide and 0.2 g stannous octoate catalyst were mixed with 50 g dichloromethane and reacted at 160 °C for 8 h. After the reaction, the product precipitate was washed and purified with anhydrous methanol and dried under vacuum to obtain the solid product. (3) Using dilute sulfuric acid as a catalyst, 3 g of the solid product from step (2) was mixed with 3 g of the linear amphoteric epoxy polyethylene glycol from step (1) and stirred. The reaction was carried out at 65°C for 75 min. Ammonium bicarbonate was added to quench the reaction. After the reaction was completed, the product was cooled and centrifuged to remove the precipitate. The product was then removed by vacuum distillation at 120°C for 2 h to obtain lactic acid-hydroxyacetic acid-polyvinyl alcohol block copolymer (4B-PLGA-EPEG).

[0042] Example 1 This embodiment provides a L-type polylactic acid microsphere, which is prepared by the following method: (1) Dichloromethane and ethyl acetate were mixed in a mass ratio of 10:3 as oil phase solvent. The 4B-PLGA-EPEG prepared in the preparation example and polylactic acid L-coated were mixed in a mass ratio of 1:1 and added to the aforementioned oil phase solvent. The total solute concentration was 0.06 g / mL, and an oil phase organic solution was obtained. (2) The oil phase organic solution was placed in a syringe and injected through an SPG membrane (20 μm) at a rate of 2 mL / min using a syringe pump to add it to a polyvinyl alcohol aqueous solution (0.03 g / mL). The mass ratio of polyvinyl alcohol aqueous solution to dichloromethane was 17:1. The mixture was stirred at 26℃ and 1000 rpm for 10 h to obtain crude product of L-polylactic acid microspheres. (3) After centrifugation and water washing to remove emulsifier and oil phase solvent, the crude product of L-polylactic acid microspheres was placed in sodium hydroxide solution at 25°C for 6 min for hydrolysis. After washing with deionized water, it was placed in polylysine solution and stirred for 20 min. The concentrations of the crude product of L-polylactic acid microspheres in sodium hydroxide solution and polylysine solution after water washing were 10 mg / L and 5 mg / L, respectively. After washing and freeze-drying, L-polylactic acid microspheres were obtained.

[0043] Example 2 This embodiment provides a L-type polylactic acid microsphere, which is prepared by the following method: (1) Dichloromethane and chloroform were mixed in a mass ratio of 2:1 as oil phase solvent. The 4B-PLGA-EPEG prepared in the preparation example and polylactic acid L-O were mixed in a mass ratio of 1:1 and added to the aforementioned oil phase solvent. The total solute concentration was 0.06 g / mL, and an oil phase organic solution was obtained. (2) The oil phase organic solution was placed in a syringe and injected through an SPG membrane (20 μm) at a rate of 2 mL / min into a polyvinyl alcohol aqueous solution (0.03 g / mL). The mass ratio of polyvinyl alcohol aqueous solution to dichloromethane was 16:1. The mixture was stirred at 26℃ and 800 rpm for 10 h to obtain crude product of L-polylactic acid microspheres. (3) After centrifugation and water washing to remove emulsifier and oil phase solvent, the crude product of L-polylactic acid microspheres was placed in sodium hydroxide solution for hydrolysis at 25°C for 10 min. After washing with deionized water, it was placed in polylysine solution and stirred for 15 min. The concentrations of the crude product of L-polylactic acid microspheres in sodium hydroxide solution and polylysine solution after water washing were 10 mg / L and 5 mg / L, respectively. After washing and freeze-drying, L-polylactic acid microspheres were obtained.

[0044] Example 3 This embodiment provides a L-type polylactic acid microsphere, which is the crude L-type polylactic acid microsphere obtained by step (2) of Example 1. The only difference between it and Example 1 is that the final drying method in step (3) is changed from freeze drying to hot drying at 45°C. The remaining steps and related process parameters are the same as in Example 1.

[0045] Example 4 This embodiment provides a L-type polylactic acid microsphere, which differs from Example 1 only in that the polyvinyl alcohol aqueous solution in step (2) is replaced with an equal amount and concentration of gelatin aqueous solution. The remaining steps and related process parameters are the same as in Example 1.

[0046] Example 5 This embodiment provides a L-type polylactic acid microsphere, which differs from Example 1 only in that the polyvinyl alcohol aqueous solution in step (2) is replaced with an equal amount and concentration of Tween-80 aqueous solution. The remaining steps and related process parameters are the same as in Example 1.

[0047] Example 6 This embodiment provides a polylactic acid (PLA) microsphere, which differs from Example 1 only in that the mass ratio of 4B-PLGA-EPEG to PLA is 2:1. All other steps and related process parameters are the same as in Example 1.

[0048] Example 7 This embodiment provides a polylactic acid (PLA) microsphere, which differs from Example 1 only in that the mass ratio of 4B-PLGA-EPEG to PLA is 3:1. All other steps and related process parameters are the same as in Example 1.

[0049] Example 8 This embodiment provides a L-type polylactic acid microsphere, which differs from Example 1 only in that the SPG membrane used has a pore size of 10 μm. All other steps and related process parameters are the same as in Example 1.

[0050] Example 9 This embodiment provides a L-type polylactic acid microsphere, which differs from Example 1 only in that the SPG membrane used has a pore size of 30 μm. All other steps and related process parameters are the same as in Example 1.

[0051] Example 10 This embodiment provides a L-type polylactic acid microsphere, which differs from Example 1 only in that the SPG membrane used has a pore size of 50 μm. All other steps and related process parameters are the same as in Example 1.

[0052] Example 11 This embodiment provides a L-type polylactic acid microsphere, which differs from Example 1 only in that the polyvinyl alcohol aqueous solution (0.03 g / mL) in step (2) is replaced with a polyvinyl alcohol aqueous solution (0.1 g / mL). The remaining steps and related process parameters are the same as in Example 1.

[0053] Example 12 This embodiment provides a L-type polylactic acid microsphere, which differs from Example 11 only in that the polyvinyl alcohol aqueous solution (0.1 g / mL) in step (2) is replaced with a gelatin aqueous solution (0.1 g / mL). The remaining steps and related process parameters are the same as in Example 1.

[0054] Example 13 This embodiment provides a L-type polylactic acid microsphere, which differs from Example 11 only in that the polyvinyl alcohol aqueous solution (0.1 g / mL) in step (2) is replaced with a mixed aqueous solution of polyvinyl alcohol and gelatin (0.1 g / mL), wherein the mass ratio of polyvinyl alcohol and gelatin is 1:1, and the remaining steps and related process parameters are the same as in Example 1.

[0055] Example 14 This embodiment provides a L-type polylactic acid microsphere, which differs from Example 11 only in that the polyvinyl alcohol aqueous solution (0.1 g / mL) in step (2) is replaced with Tween-80 aqueous solution (0.1 g / mL). The remaining steps and related process parameters are the same as in Example 1.

[0056] Example 15 This embodiment provides a L-type polylactic acid microsphere, which differs from Example 11 only in that the polyvinyl alcohol aqueous solution (0.1 g / mL) in step (2) is replaced with a mixed aqueous solution of polyvinyl alcohol and Tween-80 (0.1 g / mL), wherein the mass ratio of polyvinyl alcohol and Tween-80 is 1:1, and the remaining steps and related process parameters are the same as in Example 1.

[0057] Example 16 This embodiment provides a L-type polylactic acid microsphere, which differs from Example 11 only in that the polyvinyl alcohol aqueous solution (0.1 g / mL) in step (2) is replaced with a mixed aqueous solution of Tween-80 and gelatin (0.1 g / mL), wherein the mass ratio of Tween-80 and gelatin is 1:1, and the remaining steps and related process parameters are the same as in Example 1.

[0058] Example 17 This embodiment provides a L-type polylactic acid microsphere, which differs from Example 11 only in that the polyvinyl alcohol aqueous solution (0.1 g / mL) in step (2) is replaced with a vinylpyrrolidone aqueous solution (0.1 g / mL). The remaining steps and related process parameters are the same as in Example 1.

[0059] Comparative Example 1 This comparative example provides L-polylactic acid microspheres, which differ from Example 1 only in that 4B-PLGA-EPEG is replaced with an equal amount of L-polylactic acid. All other steps and related process parameters are the same as in Example 1.

[0060] Test Example 1 The morphology of the L-type polylactic acid microspheres prepared in Examples 1-7 and Comparative Example 1 was observed using scanning electron microscopy. The results of Example 1 are as follows: Figure 2 As shown, the imaging results of Examples 2, 3, 4, and 6 are as follows: Figure 3 As shown; and further tested the natural degradation of the L-type polylactic acid microspheres prepared in Examples 1, 6-7 and Comparative Example 1 in a near-human environment.

[0061] Take 35 mg of microspheres prepared in the examples and comparative examples respectively, wash with deionized water, place in a sealed container (37°C), and add 5 mL of PBS buffer; remove the microsphere material at the set time points; wash and dry: wash the surface of the microspheres with deionized water to remove residual buffer, freeze-dry to constant weight, record the mass loss data at different time points, plot the degradation curve, and evaluate the degradation rate of the microspheres. The results are as follows. Figure 6 As shown.

[0062] The results showed that the L-type polylactic acid microspheres prepared in Examples 1-2 had excellent monodispersity and the particle size was controlled at a small level.

[0063] (1) Comparing Example 1 and Example 3, it can be seen that when hot drying is used instead of freeze drying, the L-type polylactic acid microspheres prepared in Example 3 show adhesion and aggregation between microspheres, exhibiting solid caking. Combined with SEM imaging results, it can be seen that the microsphere material prepared in Example 3 has a large number of cracks, resulting in incomplete internal structure and micromorphological morphology of the microspheres, microsphere breakage, and a significant reduction in the efficiency of sphere formation. It can be seen that different drying methods have a certain impact on the macroscopic physical morphology of L-type polylactic acid microspheres. The L-type polylactic acid microsphere material prepared by the low-temperature freeze drying process in this invention has high sphere formation efficiency and complete structure.

[0064] (2) Comparing Example 1 with Examples 4-5, it can be seen that the scanning electron microscope images of the L-type polylactic acid microspheres prepared in Example 4 show that there is a large amount of adhesion between the microspheres, and the formed microspheres are spindle-shaped with irregular size and shape; the L-type polylactic acid microspheres prepared in Example 5 have uneven particle size distribution and dispersed size distribution, and a large amount of foam appears during the stirring reaction in step (2), which affects the stability of the subsequent microsphere formation process. This indicates that the choice of emulsifier has an important influence on the spheroidization of L-type polylactic acid microspheres in the later stage. The surface tension of the small droplets formed by the initial emulsion is not the same for the same concentration of emulsifier aqueous solution, which directly affects the stability of the subsequent microsphere solidification process.

[0065] (3) Comparing Example 1 with Examples 6-7 and Comparative Example 1, it can be seen from the degradation relationship diagram that the microspheres formed by adding L-polylactic acid and lactic acid-glycolic acid-polyvinyl alcohol block copolymer in different proportions to the oil phase solvent under the same conditions, the degradation rate of microspheres with a higher proportion of L-polylactic acid is slower than that of microspheres with a lower proportion, and the morphology of the microspheres is more stable. The degradation rate of microspheres can be adjusted by adding lactic acid-glycolic acid-polyvinyl alcohol block copolymer, but it has a certain impact on the morphology and structure of microspheres during the degradation process. Therefore, the L-polylactic acid microspheres prepared by the preparation method provided in this invention can be used to obtain L-polylactic acid microsphere materials with different degradation rates by adjusting the proportion of L-polylactic acid and lactic acid-glycolic acid-polyvinyl alcohol block copolymer.

[0066] Test Example 2 This test example uses a laser particle size analyzer to measure the particle size of the L-type polylactic acid microspheres prepared in Examples 1 and 8-10. The specific steps are as follows: Material preparation: Ensure that the L-polylactic acid microsphere samples prepared in Examples 1 and 8-10 are free from agglomeration and clumping before testing; Instrument calibration: The instrument was calibrated using 10 μm polystyrene standard particle size microspheres. The standard deviation was less than 2%. It was confirmed that there were no impurities remaining in the mobile phase tube. The test temperature was set to 25℃. Sample preparation: Take 50 mg of the L-polylactic acid microsphere samples prepared in Examples 1 and 8-10 respectively, and disperse them by ultrasonication with polyvinyl alcohol aqueous solution (0.03 g / mL); Experimental test: The rotation speed of the polyvinyl alcohol aqueous solution was set to 400 rpm, the stabilization time was 5 min, the injection volume was 2 mL each time, and each sample was tested 3 times. The average value of the particle size distribution was taken.

[0067] Experimental results record: Record the microsphere size (retain two decimal places) and standard deviation (retain three decimal places) for each experimental sample. The results are shown in the table below.

[0068] Table 1 Analysis of the data in the table shows that the size of L-polylactic acid (PLA) microspheres and the pore size of the SPG membrane used exhibit a clear positive correlation. Appropriately changing the pore size of the SPG membrane can alter the final size of the L-PLA microspheres. The small standard deviation of all tested samples indicates that the L-PLA microspheres prepared using the SPG membrane method have good uniformity, and the repeatability of the L-PLA microsphere preparation process using the SPG membrane method is relatively stable.

[0069] Test Example 3 This test example characterizes the L-type polylactic acid microspheres prepared in Examples 11-17, and the results are shown in the table below.

[0070] Table 2 Analysis of the data in the table shows that, in terms of size and particle size distribution, at lower dispersant kinematic viscosity, higher kinematic viscosity results in relatively smaller microspheres and narrower particle size distribution. This indicates a certain positive correlation between dispersant kinematic viscosity and microsphere particle size distribution. However, higher dispersant kinematic viscosity can negatively impact microsphere size and adhesion. Regarding the SPG membrane hydrophilic-lipophilic balance value, a higher SPG membrane hydrophilic-lipophilic balance value indicates a lower risk of microsphere adhesion; therefore, solvents with high SPG membrane hydrophilic-lipophilic balance values ​​should be preferred.

[0071] Comprehensive analysis shows that polyvinyl alcohol can be combined with other solvents to balance size, distribution and adhesion to a certain extent, but its performance is weaker than that of pure polyvinyl alcohol dispersants. Using pure polyvinyl alcohol dispersants can produce L-type polylactic acid microspheres with moderate size and narrow distribution, while avoiding adhesion.

[0072] The applicant declares that the technical solution of this invention is illustrated by the above embodiments, but this invention is not limited to the above embodiments, that is, it does not mean that this invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvements to this invention, equivalent substitutions of raw materials for the product of this invention, addition of auxiliary components, and selection of specific methods, etc., all fall within the protection scope and disclosure scope of this invention.

[0073] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.

[0074] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.

Claims

1. A method for preparing L-polylactic acid microspheres with controllable degradation rate for use in drug delivery systems, characterized in that, The preparation method includes the following steps: The oil phase organic solution was added to the emulsifier aqueous solution through an SPG membrane and stirred to obtain crude L-polylactic acid microspheres. The crude L-polylactic acid microspheres were then mixed and reacted with sodium hydroxide solution and polylysine solution in sequence. After washing and freeze-drying, L-polylactic acid microspheres were obtained. The solutes in the oil phase organic solution include L-polylactic acid and lactic acid-glycolic acid-polyethylene glycol block copolymer; The raw materials for preparing the L-type polylactic acid microspheres, by mass fraction, include 10-15 parts of oil phase organic solution, 150-200 parts of emulsifier aqueous solution, 70-100 parts of sodium hydroxide aqueous solution, and 70-100 parts of polylysine aqueous solution. The preparation method of the lactic acid-glycolic acid-polyethylene glycol block copolymer includes the following steps: S1. Polyethylene glycol and benzyltriethylammonium chloride are mixed with sodium hydroxide solution, heated and stirred, epichlorohydrin is added dropwise, and stirring is continued. After the reaction is completed, the filtrate is collected by filtration, washed with dichloromethane, dried, evaporated and concentrated for recrystallization to obtain linear amphoteric epoxy polyethylene glycol. S2. Ply lactide, glycolide, stannous octoate and dichloromethane are mixed with pentaerythritol and reacted under a nitrogen atmosphere. After the reaction is completed, the mixture is centrifuged, the supernatant is removed, the precipitate is washed with anhydrous methanol and dried to obtain a solid product. S3. The linear amphoteric epoxy polyethylene glycol obtained in step S1 and the solid product obtained in step S2 are mixed and reacted with dilute sulfuric acid. Ammonium bicarbonate is added to quench the reaction, the supernatant is collected by centrifugation, and the supernatant is distilled under reduced pressure to obtain the lactic acid-glycolic acid-polyethylene glycol block copolymer. In particular, the order of reactions in steps S1 and S2 is not distinguished. The concentration of solute in the oil phase organic solution is 0.05-0.15 g / mL; The emulsifier in the emulsifier aqueous solution is polyvinyl alcohol; The concentration of the emulsifier in the aqueous emulsifier solution is 0.01-0.20 g / mL.

2. The preparation method according to claim 1, characterized in that, The solvent in the oil phase organic solution includes any one or a combination of at least two of dichloromethane, ethyl acetate, chloroform, acetone, tetrahydrofuran, or propylene carbonate.

3. The preparation method according to claim 1, characterized in that, The oil-phase organic solution is added to the emulsifier aqueous solution via injection through an SPG membrane.

4. The preparation method according to claim 3, characterized in that, The injection rate is 1-3 mL / min.

5. The preparation method according to claim 1, characterized in that, The stirring speed for the reaction is 600-1200 rpm, the time is 10-16 h, and the stirring temperature is 20-30℃.

6. The preparation method according to claim 1, characterized in that, The washing method is centrifugal washing.

7. The preparation method according to claim 6, characterized in that, The centrifugal washing process involves a rotation speed of 8000-12000 rpm, a time of 5-10 min, and a temperature of 10-30℃.

8. A L-type polylactic acid microsphere material prepared by the preparation method according to any one of claims 1-7.

9. The use of the L-polylactic acid microsphere material according to claim 8 in the preparation of products with drug delivery function.

Citation Information

Patent Citations

  • Amino-modified poly-L-lactic acid drug-loaded microspheres as well as preparation method and application thereof

    CN117838922A

  • L-polylactic acid microspheres as well as preparation method and application thereof

    CN120904484A

  • KR20200127964A